GAMBARAN TINGKAT KEMANDIRIAN ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN DARUSSAADAH KECAMATAN KAMPAR KABUPATEN KAMPAR - Nurhayati Nurhayati; Zulkifli Zulkifli; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to re-analyze the degree of independence of children aged 3-4 years in play group darussa'adah districts Kampar regency of Kampar. This research is a descriptive research. The sample in this study were all members of a population of 17 children aged 3-4 years (saturated sample). Research held techniques by observation and dokumnetasi. The study begins by formulating the research problem, then proceed with searching for relevant research results analyzed. Category independence of children is determined by score indicator, the indicator The independence of children aged 3-4 years are as follows patiently wait their turn, eating and drinking themselves to wash hands before and after meals, tidy up toys after playing, brush their own teeth Measurement of these students classical instrument independence is done = 1, no = 0. The study was conducted independence of children ages 3 -4 years explained that in play group Darussa'adah Tanjung Berulak village regency of Kampar. Having carried out the research, explained that the independence of children ages 3 -4 years in play group Darussa'adah Tanjung Berulak Kampar District that are in the independent category with a score range of 16-19 or 61-80Keywords: Level of Independence